Intraspecific variation of early Cambrian (stage 3) arthropod Retifacies abnormalis revealed by morphometric analyses - Lin, Weiliang; Pates, Stephen; Losso, Sarah R.; Fu, Dongjing (Frontiers in Ecology and Evolution, 2024)
Retifacies abnormalis is a large artiopodan euarthropod known only from the famous fossil deposits of the Chengjiang biota, China (Cambrian Series 2, Stage 3). It is well known for its pronounced reticulated ornamentation that covers the entire dorsal surface of the exoskeleton. Here 109 new specimens of R. abnormalis from multiple deposits are reported. Some larger specimens display a distinct carapace ornamentation to what was previously known. By qualitatively separating specimens into two groups ('Morph A', 'Morph B') and analyzing the shape of the body, pygidium, and shape of the polygons in the reticulation, using linear and geometric morphometrics and elliptical Fourier analysis, the two morphs are shown to overlap in morphospace and display similar length:width ratios of body parts, rather than form two distinct clusters. The differences are interpreted as intraspecific rather than as diagnosing two species. As Morph B are only found in larger size classes, R. abnormalis ornamentation differences are interpreted to have developed during ontogeny, but are not thought to represent sexual dimorphs.